How does renewable energy technology innovation affect the upgrading of industrial structure? The moderating effect of green finance. (September 2022) - Ge, Tao; Cai, Xuesen; Song, Xiaowei
Abstract: In the context of sustainable development, the renewable energy technology innovation (RETI) may have a potential impact upon the industrial structure upgrading, while green finance will play a moderating part. This paper studies the role of green finance and renewable energy technological innovation on industrial structure in China. We found that RETI has contributed significantly to the adjustment of industrial structure. The research results of PVAR (Panel Vector Autoregressive) model further prove this dynamic and continuous positive promotion. The threshold regression results indicate that with the improvement of green finance, there is a non-linear relationship between RETI and industrial structure. In areas where green finance is relatively low, RETI can inhibit the upgrading of industrial structure. When the degree of green finance development is relatively high, the influence of RETI on industrial structure is remarkably positive. Heterogeneity analysis shows that in eastern China, renewable energy technological innovation has significantly promoted the industrial structure upgrading. Therefore, policy makers should take various measures to expedite the green finance development and strengthen the green finance support to renewable energy technology innovations. Chinese government has the need to continue to implement related green credit policies and expand the source of green funds. Highlights: Study the impact of renewable energy technology innovation on industrial structure. Green finance is a moderating variable. Threshold regression model is used to study nonlinear relationship. Renewable energy technology innovation positively impacts industrial structure. Green finance has a positive moderating effect.